COVID-19 Pandemic. Urgent need for increased blood donor campaigns to raise awareness on blood donation in the midst of Social Distancing. - Erhabor Osaro , Erhabor Tosan, Adias Teddy Charles , Erhabor, U. (Sokoto Journal of Medical Laboratory Science)
Voluntary non-remunerated donation of blood out of altruism saves millions of lives daily across the globe. The outbreak of SAR-COV-2 the virus responsible for COVID-19 which was first discovered in Jianghan District, Wuhan, Hubei province in China in 2019 and the declaration of the outbreak as a pandemic by WHO on the 11th March 2020 has generated a number of challenges including the provision of safe and adequate supply of blood and blood products (American Association of Blood Banks, 2019). To help reduce the transmission of the virus, social distancing measures requiring that people stay at least 1 metre apart have been put in place in most countries to reduce social interaction between people. These measures have the potential to reduce the supply of blood and blood components. There is the urgent need for blood transfusion services across the globe to put measures in place and take actioned planned steps (World Health Organization, 2019). This is to facilitate an evidence- based assessment and planning to ensure appropriate response to ensure blood supply sufficiency and unhindered delivery of safe blood and blood products to support patients including those with COVID-19 presenting with severe sepsis and hypoxaemia requiring extracorporeal membrane oxygenation (Gehrie et al., 2020; Shan et al., 2004). There is need for increased awareness, campaigns and dissemination of accurate information to facilitate increased blood donation and reduce the misconception and fears that people have about donating blood during this COVID-19 era (Yahia, 2020).